Pelatihan Peningkatan Dasar Kepemimpinan Untuk Membentuk Jiwa Kepemimpinan Yang Kreatif Dan Inovatif Pada Pengurus Yayasan Darul Furqon Ramadhan Desa Cibadung Gunung Sindur - Rahmayanti, Rahmayanti; Arifin, Zaki Zainal; Rufeidah, Annie; Benazir, Dyas Mulyani; Oktarini, Riri (LPPM Universitas Pamulang, 2020)
Leadership is the ability of someone in an organization to lead or guide others or members of the organization. The Qur'an memorization boarding school (PPA)